KOLONISASI Mus musculus ALBINO DI LABORATORIUM LOKA LITBANG P2B2 BANJARNEGARA - Dewi Marbawati; Bina Ikawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2009)
The improvement and development of science and technologycal in health area must be followed with improvement of requirement of test animal would especially white mouse (Mus musculus albino/mencit). Usage of white mouse (mencit) because of relatively easy in handling, the size relatively small, the price relatively cheap, once birth can reach 16 - 18, have similiarity in circulation system of human and doesn't have ability to vomit because having spillway in bouncing up, that is why white mouse used for drug trial research. This research expected to obtain stable white mouse colony in laboratory to fulfill requirement of white mouse as subject for research.Research was started in March-November 2008 in Loka Litbang P2B2 Banjarnegara. This research was elementary research with observational design. Data were collected from white mouse growth observation.Result of observation showed reproduction of white mouse after 5 month, from 6 white mouse increased become 17 ( increased 2 times more ), with number of deaths 11,76 %. This white mouse survive until 12 months, but the average was 6 month. Oldest mencit until research ends ( November 2008) ranges from 8 months. Daily observation data showed that white mouse can bear children until 6/pregnance. According to literature study mouse can bear children average 6 8/pregnance. Generaly baby mouse was around 1 gram, heavily borns depend on type ( strain) of white mouse. Result of white mouse weight showed increase of white mouse's body weight every 2 weeks was 8,6 grams. Observation data of development white mouse showed after 4 days the white mouse hair was seen, specially moustache that was clearly seen, on 5 day whole body was white. At the age of 10 days ear opened, part of other body like external mamilla and genitals become explains looked to be. At the age of 12 days eye started opens and active walking.